ASPECTS OF THE THERAPY OF PARTIALLY EXTENDED EDENTATION USING MODERN METHODS - ATTACHMENTS AS MAINTENANCE, SUPPORT AND STABILIZATION - Magda-Ecaterina Antohe; Doriana Agop Forna; Monica Andronache; Ramona Feier; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2016)
Attachments are support and stabilization elements which ensure both a superior esthetics as compared to the use of clasps and a very good biomechanical balance, provided that the basic principles of the skeletal removable prosthesis design are met.Aim : The purpose of this study is the thorough detailing of the main aspects that influence the therapy of partially extended edentation through modern means, using support and stabilization elements such as extracoronal removable attachments, with the identification of the individualization elements in agreement with this type of therapeutic solution. Material and Method:The study lot was made up of a number of 50 patients diagnosed with partially extended and subtotal edentation who reported to the clinical facility of the Faculty of Dental Medicine during 2014-2016. The lot comprises 30 women and 20 men, aged between 38 and 73. We evaluated the pacients clinical and paraclinical.Results and Discussions: Regarding the status of local indices, obviously in correlation with the other factors that decisively influence the therapeutic decision, we notice a percentage equality of 50% between the positive and negative clinico-biological indices, a very important aspect in the therapeutic decision to make a hybrid prosthesis that uses as maintenance, support and stabilization extracoronal removable attachments, which can only be used in case of a very good dental implantation.Conclusions :In the elaboration of the therapeutic decision of hybrid prosthesis that uses as maintenance, support and stabilization elements extracoronal removable attachments we need to take into account the limits set by this prosthesis, dictated by the topography of dental elements on the arch, as well as by the odonto-periodontal status of the elements involved.